Analisis pengaruh struktur modal terhadap profitabilitas perusahaan yang terdaftar di BEI - Devanti, Dila Adelia; Sugiharto, Sugiharto; Prihadyatama, Ardila (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The capital structure of a business directly affects its profitability. The profitability of a company is directly correlated to its capital structure. The purpose of this study is to analyze the relationship between capital structure and financial performance. An empirical study best describes this sort of research. For the years 2016–2020, PT H. M. Sampoerna was the sample that was utilized. This study employs quantitative methods for data analysis. This study's findings reveal that ROA and ROE, two measures of profitability, are influenced by capital structure variables such as the Debt Ratio (DR) and the Debt to Equity Ratio (DER). Mathematical analysis of PT H. M. Sampoerna's processed financial reports from 2016 to 2020 reveals that a higher Debt Ratio (DR) has an effect on the company's profit level, with a lower profit level being the result of a higher debt value. A higher Debt to Equity Ratio (DER) indicates that a larger amount of capital is required to cover the debt, but a lower amount of profit is produced by the business.